Aqueous micro and nanoreactors based on alternating copolymers of phenylmaleimide and vinylpyrrolidone bearing pendant l‐proline stabilized with PEG grafted chains. Issue 7 (3rd February 2017) - del Prado, Anselmo; Pintado‐Sierra, Mercedes; Juan‐y‐Seva, Marta; Navarro, Rodrigo; Reinecke, Helmut; Rodríguez‐Hernández, Juan; Elvira, Carlos; Fernández‐Mayoralas, Alfonso; Gallardo, Alberto
ABSTRACT: Proline may work efficiently in water as catalyst of aldol reactions if it is hydrophobically activated. In this work, we have maximized this hydrophobic activation by the preparation of linear alternating copolymers of hydrophobic phenylmaleimide and a vinylpyrrolidone derivative bearing proline. These copolymers were water soluble above pH 5.0 and, unlike the free proline, exhibited efficient catalysis at pH 7.0. Moreover, they catalyzed and presented enantioselectivity in an aggregated form at pH 4.0 (close to the isoelectric point, IEP, of the polymer). This enantioselectivity has been related to the exclusion of water at this IEP. To control the size and stabilize the aggregates, PEG grafted copolymers were prepared by the incorporation of a PEG‐macromer (2–10 mol%), which rendered stable nano‐aggregates in water at the IEP. At this pH they catalyzed the aldol reaction in a higher rate than the non‐grafted polymer, but the enantioselectivity was decreased. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 55, 1228–1236 Abstract : Proline needs a hydrophobic environment free of water to be catalytically efficient in water. In this work efficient and biomimetic catalysts, with maximized hydrophobic activation, have been obtained by preparing linear alternate copolymers of proline and aromatic‐containing moieties, while the exclusion of water has been achieved by working at the isoelectric point. The grafting of PEO chains has provided colloidal stabilization and higher rates at the expense of the stereoselectivity.